A dose‐ranging study of ticagrelor in children aged 3‐17 years with sickle cell disease: A 2‐part phase 2 study. Issue 12 (2nd October 2018) - Hsu, Lewis L.; Sarnaik, Sharada; Williams, Suzan; Amilon, Carl; Wissmar, Jenny; Berggren, Anders; ,
Abstract: Antiplatelet treatment is a potential therapeutic approach for sickle cell disease (SCD). Ticagrelor inhibits platelet aggregation and is approved for adults with acute coronary syndrome and following myocardial infarction. HESTIA1 (NCT02214121) was a 2‐part, phase 2 dose‐finding study generating ticagrelor exposure, platelet inhibition, and safety data in children with SCD (3‐17 years). In part A ( n = 45), patients received 2 ticagrelor single doses, 0.125‐2.25 mg/kg (washout ≥7 days), then 7 days of twice‐daily (bid) dosing with 0.125, 0.563, or 0.75 mg/kg. In the 4‐week blinded Part B extension (optional), patients received ticagrelor (0.125, 0.563, or 0.75 mg/kg bid; n = 16) or placebo ( n = 7). Platelet reactivity decreased from baseline to 2 hours postdosing, and returned to near baseline after 6 hours postdosing. Dose‐dependent platelet inhibition was seen with ticagrelor; mean relative P2Y12 reaction unit inhibition 2 hours after a single dose ranged from 6% (0.125 mg/kg) to 73% (2.25 mg/kg). Ticagrelor plasma exposure increased approximately dose proportionally. No patients experienced a hemorrhagic event during treatment. No differences were seen between groups in pain ratings and analgesic use during Part B. Ticagrelor was well tolerated with no safety concerns, no discontinuations due to adverse events (AEs), and reported AEs were mainly due to SCD. In conclusion, a dose‐exposure‐response relationship for ticagrelor was demonstrated in children with SCD for the first time. These data are important for future pediatric studies of the efficacy and safety of ticagrelor in SCD.